Feasibility Analysis of Rumah Produksi Bersama (RPB) for Chili Commodities as Investment Promotion in Batubara Regency, North Sumatra - Susanto, Heri; Suwarnata, Anak Agung Eka; Ariesta, Nina; Maad, Faizal (Jurnal Logistik Indonesia, 2024)
Chili is a strategic agricultural commodity that has high economic value and makes a real contribution to the national economy. The biggest problem in the chili trade system is price stabilization. Unstable prices occur when there is a change in supply volume. Based on BPS data in 2021, North Sumatra is the largest chili center outside Java with a contribution of 14.16%. Followed by West Sumatra and Aceh contributing 8.27% and 4.6% respectively. The center for red chili production in North Sumatra Province is Batu Bara Regency, which has an area of 982 ha with a productivity of 8 tons/hectare for red chilies, apart from Karo, Simalungun and Dairi. One way to overcome the chili problem in Batu Bara Regency is with the Rumah Produksi Bersama (RPB) program, which is a place for micro and small business actors to carry out joint production activities with similar product commodities, dependence on similar workforce skills, or the use of complementary technologies. Apart from that, RPB is a promotion for regional government investment in developing their region (Regional Branding) in addition to differentiating products and increasing value. For this reason, a Feasibility Study Method for the RPB KUKM for chili commodities in Batu Bara Regency, North Sumatra Province is needed, including through location, Production, Marketing, Financial and Management analysis as well as reviewing the regional image. Based on the results of the feasibility study, it was found that the location of the RPB is in chili, Lubuk Cuik Village, Limapuluh Pesisir District, Batu Bara Regency, North Sumatra Province, which is not far from the chili center in Batu Bara Regency. To achieve feasibility in accordance with the capabilities of RPB cutlery, it must be able to produce a minimum of 20 tons per month or around 240 tons per year with this production NPV, IRR and PP can be said to be feasible. Meanwhile, marketing is carried out B2B and B2C for potential offtakers, apart from building public-private partnerships and involving all key stakeholders, with the main player being the government.